Waqf and Islamic Economics: Evidance on Establishing Student House - Furqonul Haq; Muhammad Zainul Wathani (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2019)
In the last decade, Ghirrah related to the practice of Waqf in Indonesia is increasing in terms of quantity and diversity. For example, continue to increase the land/object of Waqf, the more new institutions that manage the Waqf, the existence of associations and forums for the development of Waqf, and the presence of new types of Waqf, such as insurance. Waqf is a proven system that can contribute to progress, culture, education, economics, social and civilization. In Islam Waqf has been practiced since the time of Rasulullah SAW and has undergone many significant changes ranging from its type, management and purpose. All that demands a new ijtihad ijtihad that can provide an alternative development of Waqf in the present that does not contradict the Islamic Shari'a. The purpose of this article is to highlight the importance of waqf in establishing student house. Nowadays, worthed boarding house is costly and this has prevented students from getting worthed boarding house. This paper offer an alternative solution to relieve such a situation, namely, through the application of waqf. The study suggests a concept to establish Waqf student house. The data was mainly collected using library research, all the data were analysed using the content analysis method. The findings show that waqf student house can help and support education in university. This article provides simulation scheme for establishing student house through waqf